Music Discovery: Past, Present, and Future. - Holden, Chris; Knop, Keith; Newcomer, Nara (Notes, 2019)
Those designing library discovery systems are presented with numerous challenges, many of which relate to "non-book materials" such as music scores and recordings. Generally, cataloging rules and search or discovery systems are optimized for text written "about" a specific subject or works bearing distinctive, consistent titles. Music scores and recordings do not routinely have distinctive titles, and they exist in a multiplicity of formats. Two additional issues affect users' ability to retrieve music results: a bias toward Western art music and users' expectations based on familiarity with the "one search box approach" found in commercial online retailers' Web sites. This article explores the history of music librarians' efforts to facilitate discovery of music materials. By examining the problems inherent in music discovery and the attempts to solve them through cataloging and discovery systems, the history provided here ends with the release of the Music Discovery Requirements 2 (MDR2): recommendations for those who are guiding the development of discovery interfaces which include music materials, and those who are developing standards for recording and encoding data. Four music-specific issues along with MDR2's recommendations are explored in detail.